Key Steps of Ukraine in the Military and National Security System to Increase Cognitive Resilience (2025-2028): Recommendations in the Cognitive and Military-Economic Spheres - Semenenko, Oleh; Kin, Oleksandr; Semenenko, Liliia; Remez, Volodymyr; Mytchenko, Serhii; Rybak, Dmytro (Social Development and Security, 2025)
Purpose. Outline the key steps of Ukraine in 2025–2028 in the military and national security system, aimed at increasing the cognitive resilience of society and the defense sector, taking into account the threats of the Russian-Ukrainian war, global trends in information confrontation, and the economic challenges of the war. Method. Methods of analysis and synthesis; comparison; strategic analysis. Findings. Ukraine’s key steps to increase cognitive resilience in 2025–2028 were identified under various scenarios of the development of the Russian-Ukrainian war; a system of military-economic consequences of cognitive influence was formed; a holistic description of Ukraine’s key steps for 2025–2028 to increase its own cognitive resilience and, at the same time, a systematic, legitimate influence on the consciousness of Russians - citizens, elites and target groups.. Theoretical implications. The results of the study can be used by specialists of higher-level military command bodies to form views on further countering cognitive threats during an ongoing war. Paper type. Theoretical.